Research Trends in The Development of Biology Learning Media in Indonesia: A Bibliometric Analysis - Kusmahardhika, Noviansyah; Mahanal, Susriyati; Balqis, Balqis; Faridha, Haidir Algi Gaffar; Ramadhan, Bramantara Haikal (JURNAL EKSAKTA PENDIDIKAN (JEP), 2024)
Several bibliometric studies have been conducted to see the progress of Biology Learning Media (BLM), but these researches still provide a broad scope in evaluating the development of BLM. This study aims to provide a holistic overview of the trends in the use of BLM in Indonesia during 2018-2023 on the Scopus database. The method used is bibliometric analysis by identifying and analyzing the growth patterns of literature, authors, institutions, and keywords related to BLM development. The research procedure consisted of investigation, reduction, compilation, and interpretation. A total of 43 articles were analyzed using VOSviewer software to visualize bibliometric mapping. For the last five years, BLM-related publications peaked in 2019 with 13 articles. Universitas Negeri Malang is a foremost institution in BLM development. The most widely used BLM are android-based media, interactive multimedia, and website-based media. Ecology is the most widely taught learning topic, while cognitive (knowledge) is the most frequently measured learning outcome. We highlighted a paradigm change in the use of more massive Technology-based learning media. In the future, we suggest exploring various research topics in biology learning such as protists, genetics, or microbiology that can empower literacy as a primary topic in more innovative and dynamic learning.